HUBUNGAN KARAKTERISTIK PETANI DENGAN PENDAPATAN USAHATANI PADI SAWAH TADAH HUJAN DI DESA MANDAHU KECAMATAN KATALA HAMU LINGU KABUPATEN SUMBA TIMUR - Amah, Yeti Njuka; Retang, Elfis Umbu Katongu; Mbana, Febyningsi Rambu Ladu (Universitas Galuh, 2023)
This study aims to analyze the relationship between farmer characteristics and income of paddy rice farming with a rainfed irrigation system in Mandahu Village, Katala Hamu Lingu District, East Sumba Regency. Research activities were carried out from October 2022 to January 2023. The sample in this study was 61 people, who are rainfed rice farmers in Mandahu Village. In order to determine the average income of the sample, an income analysis was carried out, and to determine the relationship between the characteristics of farmers and the income of farmers, a Spearman Rank Correlation Coefficient Test was carried out. The results of this study explain that the average income of a sample of rainfed lowland rice farmers in Mandahu Village is IDR 14,724,987 per hectare. The test results illustrate that the factors of age, education level, and number of dependents in the sample family have no relationship with the income of the sample. Meanwhile, the length of farming and land area of the sample are concluded to have a relationship with the income of the sample.